Agrobiodiversity and local wisdom of indigenous communities in food security in Eastern Priangan, West Java, Indonesia - ABDUL MUTOLIB; RIANTIN HIKMAH WIDI; CANDRA NURAINI; ALI RAHMAT (Society for Indonesian Biodiversity, 2026)
Abstract. Mutolib A, Widi RH, Nuraini C, Rahmat A. 2026. Agrobiodiversity and local wisdom of indigenous communities in food security in Eastern Priangan, West Java, Indonesia. Biodiversitas 27 (3): d270318. https://doi.org/10.13057/biodiv/d270318. Food security remains a persistent global challenge, shaped by population growth, climate change, and increasing pressure on natural resources. In Indonesia, despite exceptional biological and cultural diversity, food systems are increasingly threatened by land conversion, environmental degradation, and dietary homogenization. This study investigates how agrobiodiversity, traditional ecological knowledge (TEK), and social capital contribute to strengthening household food security in Kampung Naga, an indigenous Sundanese community in Eastern Priangan, West Java, Indonesia. A mixed-methods approach was employed, integrating biodiversity inventories, thematic analysis of interviews and participant observations, and a social capital survey involving 50 household respondents. Agrobiodiversity was assessed through species identification across major food categories, while social capital was measured using five dimensions—trust, social networks, social norms, participation, and reciprocity—on a four-point Likert scale. Results show that the community maintains a high diversity of food plant species, including tubers and staple foods, fruits, spices and seasonings, leafy and green vegetables, and vegetables and legumes, which enhance dietary diversity, nutritional adequacy, and livelihood resilience. Traditional ecological knowledge informs sustainable agricultural practices such as intercropping, crop rotation, and food preservation, while ritualized expressions of gratitude embed agriculture within cultural and spiritual values. Household and communal food barns further strengthen food stability and collective risk management. Social capital analysis revealed relatively high mean scores for trust (3.40) and social networks (3.45) on a 1-4 scale, indicating strong interpersonal reliability, dense social ties, and effective cooperation in food-related activities. Together, agrobiodiversity and social capital synergistically reinforce the four dimensions of food security-availability, access, utilization, and stability-forming an integrated, resilient, and socially embedded food system. These findings highlight the enduring relevance of indigenous knowledge and institutions in sustaining food security and suggest that strengthening social capital can serve as a strategic policy entry point for designing inclusive, community-based food security interventions in Indonesia and comparable socioecological contexts.